Relating Language and Music Skills in Young Children: A First Approach to Systemize and Compare Distinct Competencies on Different Levels - Cohrdes, Caroline; Grolig, Lorenz; Schroeder, Sascha (Frontiers in Psychology, 2016)
Children in transition from kindergarten to school develop fundamental skills important for the acquisition of reading and writing. Previous research pointed toward substantial correlations between specific language- and music-related competencies as well as positive transfer effects from music on pre-literacy skills. However, until now the relationship between diverse music and language competencies remains unclear. In the present study, we used a comprehensive approach to clarify the relationships between a broad variety of language and music skills on different levels, not only between but also within domains. In order to do so, we selected representative language- and music-related competencies and systematically compared the performance of N = 44 5- to 7-year-old children with a control group of N = 20 young adults aged from 20 to 30. Competencies were organized in distinct levels according to varying units of vowels/sounds, words or syllables/short melodic or rhythmic phrases, syntax/harmony and context of a whole story/song to test for their interrelatedness within each domain. Following this, we conducted systematic correlation analyses between the competencies of both domains. Overall, selected competencies appeared to be appropriate for the measurement of language and music skills in young children with reference to comprehension, difficulty and a developmental perspective. In line with a hierarchical model of skill acquisition, performance on lower levels was predictive for the performance on higher levels within domains. Moreover, correlations between domains were stronger for competencies reflecting a similar level of cognitive processing, as expected. In conclusion, a systematic comparison of various competencies on distinct levels according to varying units turned out to be appropriate regarding comparability and interrelatedness. Results are discussed with regard to similarities and differences in the development of language and music skills as well as in terms of implications for further research on transfer effects from music on language.